A pressure-based solution framework for sub- and supersonic flows considering real-gas effects and phase separation under engine-relevant conditions. (30th April 2020) - Traxinger, Christoph; Zips, Julian; Banholzer, Matthias; Pfitzner, Michael
Highlights: Presentation of an All-Mach number pressure-based numerical framework. Discussion and elaboration of thermal, mechanical and chemical instabilities. Introduction of a rigorous thermodynamic closure based on Gibbs energy minimization. Exhaustive description of the stability testing and flashing approach. Numerical investigation of phase separation in a highly underexpanded Argon jet. Abstract: The present study describes a pressure-based solution framework suitable for the numerical investigation of sub- and supersonic injection processes under high-pressure conditions. The focal point is put on the introduction of a fully consistent and rigorous thermodynamic closure based on the cubic equation of state. Hereby, both real-gas effects as well as phase separation processes can be considered resulting in a more thorough investigation of physical phenomena and an increased solver stability as the inadvertently penetration of unphysical states, i.e., the crossing of the spinodal, is prevented. To demonstrate the advantage of the numerical framework, recent experimental investigations of an underexpanded argon jet showing both real-gas and phase separation effects are used. The agreement between the experiment and the Large-Eddy Simulation is good. In particular, the phase separation process shows excellent agreement and is studied thoroughly based on the numerical results.